EFEKTIVITAS PENERAPAN KEBIJAKAN OTONOMI DAERAH DALAM PENURUNAN TINGKAT KEMISKINAN DI BANDUNG BARAT TAHUN 2019 - Muhammad Ridha Iswardhana; Attina Maulidia Selma Attamimi (LPPM Universitas Abdurrab, 2023)
West Bandung is part of the Bandung Regency which underwent regional expansion in 2007. Even though in 2017 West Bandung received the title of the best autonomous region, West Bandung has unresolved social problems in the form of high poverty, especially compared to other districts in West Java Province. Several causes of poverty in West Bandung such as low participation in education, prone to disasters, and inadequate infrastructure. This research uses descriptive qualitative using secondary sources in the form of books, journals, and articles. This study aims to determine the effectiveness of regional autonomy in West Bandung in reducing poverty. The form of regional autonomy for West Bandung Regency has not significantly reduced poverty, including the many damaged roads, inadequate infrastructure, and less responsive to disaster management. As a result, West Bandung's economy is weak causing a high poverty rate.